Impacts of Wintertime Extratropical Cyclones on Temperature and Precipitation Over Northeastern China During 1979–2016. Issue 3 (13th February 2019) - Lin, Daiyu; Huang, Wenyu; Yang, Zifan; He, Xinsheng; Qiu, Tianpei; Wang, Bin; Wright, Jonathon S.
Abstract: This study examines the synoptic impacts of wintertime extratropical cyclones on northeastern China. The 181 analyzed cyclones mainly originate from eastern Mongolia and dissipate over the North Pacific Ocean. Precursor negative geopotential height anomalies for these cyclones emerge over continental areas near the Barents and Kara Seas. Baroclinic instability and midlatitude westerly winds are the dominant factors driving the development and movement of these cyclones from their precursor signals. Owing to the southeastward migration of the cyclones, temperature over northeastern China first increases and then decreases, resulting in a significant increase in the frequency of extreme weather. These cyclones contribute about 70.6% of the extreme precipitation days over northeastern China. Relative moisture contributions from the East China Sea, the Sea of Japan, and East Asia are all anomalously large during cyclones associated with extreme precipitation days, with moisture from these regions entering northeastern China mainly through its southern and western boundaries. Temperature variations over northeastern China play a critical role in the accumulation of moisture for extreme precipitation and the timing of that precipitation. Moisture transport initially contributes to an increase in precipitable water due to warm temperature anomalies. The added precipitable water is then released as extreme precipitation when the atmosphere over northeastern China starts to cool. Key Points: Precursors for extratropical cyclones over northeastern China occur in continental areas close to the Barents and Kara Seas Extratropical cyclones initially warm then cool northeastern China Extratropical cyclones play a leading role in triggering wintertime extreme precipitation over northeastern China